Остання таємниця Богдана Хмельницького: обставини поховання і місцезнаходження могили гетьмана - Новик, М. (Народна творчість та етнографія, 2005)
The article suggests a number of hypotheses on the circumstances and location of the hetman's grave. The author doubts the existing versions of B. Khmelnytskyj' burying. He puts forward an idea that the grave is in the crypt of st. Illya Church in Subotiv. The reasons of the delay and the secrecy of the hetman's funeral are substantiated in the article. The following hypothesis is supported by the expedition of the scholars of the Institute of Archaeology in summer 2005.